Educação científica no ensino médio: produção de conhecimento através da autonomia para a pesquisa - Machado, Jober Vanderlei de Vargas (2019)
Scientific education passes by several competencies associated mainly with the understanding of scientific production, critical reading, autonomy for research and the ability to make a stand concerning scientific production. Such competencies can be developed within "curricular spaces" that allow the accomplishment of activities directed to the research and the promotion of the autonomy and protagonism of the students. This work aimed to promote the understanding of the nature of scientific production, through strategies directed to scientific education, performing an analysis that characterizes the process experienced by the students. The activities were developed within the study plan of the Integrated Seminar (IS), during the years of 2015 and 2016, with classes of High School junior students, totaling 50 students of a public school of Rio Grande do Sul state, Brazil. The activities were organized using an adaptation of the Three Pedagogical Moments and were planned from the acknowledgement of questions related to the students' professional interest; organization of research projects, collecting data and reading scientific texts; and finally the presentation of the studies for the school community and the writing of articles for the magazine “Scientific Silveira”. The methodology of the pedagogical moments had to be adapted to promote a greater protagonism and autonomy of the students since the role of the teacher was to awaken the curiosity and reflection of the students to seek the knowledge from the results obtained in the literature. Questionnaires were used to verify students' opinions in all stages of the study, initially to identify the objectives of attending high school and the perception of scientific activity, and also throughout the course. The responses were analyzed using the Discursive Textual Analysis method. Some official documents were analyzed to characterize the conception of science to be worked in the classroom and the objectives of the HS for the formation of the students. The students had difficulties regarding the reading of articles and scientific writing, and also the methodology of the IS discipline. At the end of the work, the students presented a conception of science associated with the production of new knowledge that should be disseminated to the population. In relation to the role of scientists, the students characterized them as professionals who work in several fields of research producing new knowledge. We can note that the activities developed within the IS discipline were significant for the students to experience the nature of the production of scientific knowledge in order to promote science education.